Hyperbaric Oxygen Therapy as Adjuvant Therapy in Nasopharyngeal Cancer : A Literature Review - Djatiwidodo Edi Pratiknyo Djatiwidodo (Fakultas Kedokteran, Universitas Hang Tuah, 2023)
Introduction Hyperbaric oxygen therapy (HBOT) may not be widely known. In Indonesia itself, the HBOT application was first carried out in 1960 by the Indonesian Navy Marine Health Institute / Lembaga Kesehatan Kelautan TNI AL (Lakesla) in collaboration with the Naval Central Hospital (Rumah Sakit Pusat Angkatan Laut / RSPAL) Dr. Ramelan Surabaya, where until now the facility is still the largest in Indonesia. Hyperbaric oxygen therapy was first introduced by Behnke in 1930. At that time hyperbaric oxygen therapy was only given to divers to relieve symptoms of decompression sickness (Caisson's Disease)1. Hyperbaric oxygen therapy is a treatment method using high pressure oxygen, where the pressure used is higher than atmospheric pressure (more than 1 atm). High pressure oxygen therapy methods are currently widely used as adjuvant therapy for various pathological conditions associated with hypoxic and/or ischemic conditions. The standard procedure for HBOT is to inhale pure oxygen (100% O2) using a pressure between 1.5 and 2.5 atmospheres absolute (ATA) by mask or by endotracheal tube which is the sum of the atmospheric pressure and the gauge pressure in a hyperbaric chamber2–4.